Hubungan Antara Brand Awareness, Brand Reputation, dan Brand Trust pada Restoran Lokal Berbasis Rantai di Kota Malang - Hendrawan, Dimas; Nugroho, Dian Ari (Universitas Brawijaya, Indonesia, 2016)
This study aimed to determine the effect of brand awareness to brand reputation and brand trust at local chain restaurant industry in Malang. Further more, this study aimed to determine the mediating effect of variable brand reputation between brand awareness and brand trust. This explanatory study used purposive sampling techniques by 100 respondents. Data were collected by questionnaire. Hypothesis testing used by path analysis. The resultÂ showed that the brand awareness has indirect effect to brand trust through brand reputation as intervening variable, the brand awareness has a significant effect to brand reputation, andthe brand reputation has a significant effect to brand trust.Â